2015
DOI: 10.1177/1076029615579099
|View full text |Cite
|
Sign up to set email alerts
|

Recurrence of Venous Thromboembolism in Patients With Cancer Treated With Warfarin

Abstract: Venous thromboembolism (VTE) is a common complication in patients with cancer. Previous randomized studies have demonstrated that rates of recurrent VTE are lower in patients treated with low-molecular-weight heparin compared to warfarin. We performed a retrospective analysis of 236 patients with cancer managed by a dedicated oncology anticoagulation management service to compare “real-world” rates of recurrent VTE and bleeding in patients treated with warfarin versus parenteral anticoagulants. Initial anticoa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 28 publications
0
13
0
1
Order By: Relevance
“…Anticoagulant therapy may be difficult to manage in patients with active cancer , and the physician choice for oral anticoagulant therapy may depend on type of cancer and time since cancer diagnosis. Patients with active cancer treated with VKA therapy may not meet the desired international normalized ratio (INR) interval due to hypercoagulation, interaction with oncology drugs, or concurrent conditions , but the frequencies of comorbidities did not vary substantial among cancer patients with VKA versus NOAC prescriptions in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Anticoagulant therapy may be difficult to manage in patients with active cancer , and the physician choice for oral anticoagulant therapy may depend on type of cancer and time since cancer diagnosis. Patients with active cancer treated with VKA therapy may not meet the desired international normalized ratio (INR) interval due to hypercoagulation, interaction with oncology drugs, or concurrent conditions , but the frequencies of comorbidities did not vary substantial among cancer patients with VKA versus NOAC prescriptions in our study.…”
Section: Discussionmentioning
confidence: 99%
“…40 A small retrospective study of cancer patients with VTE also noted favorable results with warfarin therapy compared with LMWH. 41 These studies suggest that VKAs may be as effective as LMWH in some cancer patients with VTE. Further research is warranted to confirm these findings.…”
Section: What Is the Risk Of Venous Thromboembolism (Vte) In Cancer Pmentioning
confidence: 94%
“…The differences in severity of cancer stage and associated complications also led to a lower event rate in the VKA arm in CATCH, resulting in an underpowered study. Improved VKA management or the use of VKAs in a population more like the CATCH trial could potentially overcome these issues, as demonstrated by a published retrospective study demonstrating the equivalence of warfarin and LMWH for prevention of VTE recurrence in cancer patients cared for in a dedicated anticoagulation clinic providing support for oncologic clinicians [ 26 ]. The TTR was 59.5% for patients treated with warfarin, and bleeding rates were similar between warfarin and LMWH-treated patients.…”
Section: Vitamin K Antagonists and Low Molecular Weight Heparins Fmentioning
confidence: 99%